Ontogenetic Changes in the Bacterial Symbiont Community of the Tropical Demosponge Amphimedon queenslandica: Metamorphosis Is a New Beginning - Fieth, Rebecca A.; Gauthier, Marie-Emilie A.; Bayes, Joanne; Green, Kathryn M.; Degnan, Sandie M. (Frontiers in Marine Science, 2016)
Vertical transmission of bacterial symbionts, which is known in many species of sponge (Porifera), is expected to promote strong fidelity between the partners. Combining 16S rRNA gene amplicon sequencing and electron microscopy, we have assayed the relative abundance of vertically-inherited bacterial symbionts in several stages of the life cycle of Amphimedon queenslandica, a tropical coral reef sponge. We reveal that adult A. queenslandica house a low diversity microbiome dominated by just three proteobacterial OTUs, with a single gammaprotebacterium clearly dominant through much of the life cycle. This ontogenetic perspective has revealed that, although vertical transmission occurs very early in development, the inherited symbionts do not maintain proportional dominance of the bacterial community at every developmental stage. A reproductive bottleneck in the A. queenslandica life cycle is larval settlement, when a free-swimming pelagic larva settles out of the water column onto the benthos and completes metamorphoses into the sessile body plan within just 3 to 4 days. During this dramatic life cycle transition, an influx of environmentally-derived bacteria leads to a major reorganization of the microbiome, potentially challenging the fidelity and persistence of the vertically-inherited symbiotic relationships. However, dominance of the primary, vertically-inherited symbionts is restored in adult sponges. The mechanisms underlying ontogenetic changes in the bacterial community are unknown, including how the dominance of the primary symbionts is restored in the adult sponge – does the host or symbiont regulate this process? Using high-resolution transcriptional profiling in multiple stages of the A. queenslandica life cycle combined with this natural perturbation of the microbiome immediately following larval settlement, we are beginning to identify candidate host genes associated with animal-bacterial crosstalk. Among the sponge host genes upregulated during the times of active microbiome assembly, there is an enrichment of genes potentially involved in innate immunity, including scavenger receptors, and of genes containing eukaryote-like domains, which have elsewhere been implicated in host-symbiont interactions. Intriguingly, we also see an enrichment of sponge genes arising from ancient horizontal transfer events from bacteria, which raises the possibility that host-bacterial associations in the evolutionary past may help to regulate host-bacterial associations in the ecological present.